The metamorphosis of the informal city in the Area Metropolitan of Buenos Aires (Revista LIDER, 2021)
There are almost a thousand informal settlements in Buenos Aires Metropolitan Area, developed according to two basic urban patterns. Both patterns correspond to different social and historic process: the “villas” or “villas miseria” (‘misery village’ in a literal translation), shanty towns mostly located in the central city of the metropolis, Ciudad Autónoma de Buenos Aires, and its first ring of municipalities; the “asentamientos”, land illegal occupations (“tomas de tierra”) located in peripherical and low density areas. Our analysis focuses in a characterization of urban informality and in the emergence of new phenomena: the informal real estate market in these settlements. We shall analyze it under a socioanthropological key, inquiring about the contending logics and “legacies” present in informal settlements and the self-managed process of neighborhood improvement, concomitants to demands to the State to provide infrastructural services and collective equipments.